Simulation of ship-ice collision dynamics. - Phillips, Loyd D. (University of Ottawa (Canada), 1994)
The Canadian government has committed substantial research funds towards improving guidelines for the structural design of commercial ships operating in northern waterways. Of particular concern is the threat to survivability presented by head-on collision with multi-year ice or fragments of icebergs. The task of developing effective numerical models for studying the collision process has been hampered by the complexity of the physical interaction mechanisms. The present research considers the nonlinear and dynamic character of this problem. A method for time-domain simulation of hullgirder stresses in icebreaking ships during collisions with multi-year ice is described. The model, ITHACA$\sb{-}$SHIP, considers the transient ship-ice interaction and fluid-structure phenomena as strongly coupled through ship dynamics. Emphasis has therefore been placed on the development of hydrodynamic and ice force models. Rigorous kinematic constraints at the interaction interface were identified as a critical factor in replicating the dynamic characteristics of prototype collision response. This led to the development of techniques for the three-dimensional mapping of this instantaneous ice boundary relative to the moving hull surface. The transient hydrodynamic force is also calculated directly, using boundary integral equation methods and a two-dimensional strip approach. The wave radiation problem for defining the free surface boundary of the fluid is based on a mixed Euler-Lagrange formulation. The prediction of hullgirder stresses is carried out in two steps. Ice and fluid interaction forces are first determined from a rigid body motions simulation, and then subsequently applied as generalized forces in an analysis of flexural response. The hullgirder bending moments and stresses are extracted from the response. The modeling methodology has been verified by predicting simulated stress results for the MV Arctic, a multi-purpose bulk carrier. Good correlation was observed between the numerical predictions and corresponding results from physical model tests and full scale ramming trials. Further discussion is given concerning whipping indicated at higher impact speeds. Nonlinearity of the ship-ice and fluid-structure interaction phenomena has been assessed by introducing progressively more complex representations of the physical mechanisms into the ITHACA$\sb{-}$SHIP model. These studies found a high degree of coupling between the two effects. The transient hydrodynamic term was shown to be a significant factor, and the importance of the kinematic criteria confirmed. The indirect representation of collision interaction forces using conventional added mass and damping coefficients in the equations of motion was shown to be conceptually incorrect. The present research has largely been limited to the development of the modeling methodology and examination of a number of suppositions concerning the collision process. But, interactive design software is available in the ITHACA$\sb{-}$SHIP model which gives it a capacity for representing realistic ship forms. It may therefore be applied more generally as an engineering tool for conceptual design and parametric analysis; either to investigate collisions with ice, or other types of obstacles, such as mud banks and reefs.
Keywords: Engineering, Civil.